Cervical Cancer Cells Use the CD95 and IL-2 Pathways to Promote Their Proliferation and Survival - Adriana Gutiérrez-Hoya; Ivan Ortiz-Garrido; Itzel Salazar-Valencia; Christopher Romero-Hernández; Arturo Valle-Mendiola; Benny Weiss-Steider; Isabel Soto-Cruz (Biomolecules)
Cervical cancer is a global health problem; therapies focused on eliminating tumour cells and strengthening different immunotherapies are in development. However, it has been observed that cervical tumour cells can evade cell death mechanisms and generate immune system molecules to promote their proliferation and metastasis. In this context, we analysed the role of the IL-2 and CD95 pathways, essential molecules in activating the immune system and eliminating tumour cells. However, it is important to analyse their role in cervical tumour cells because these cells could be using these pathways to proliferate. In this study, we found that SiHa and HeLa cells respond to treatment, with 10 IU/mL of IL-2 inducing their proliferation and 100 IU/mL of IL-2 decreasing their proliferation. We also observed that they express a high percentage of the CD95 receptor and its ligand (CD95L) and that treatment with CD95 agonist antibodies at low doses increases cell proliferation. Furthermore, simultaneous treatment with high doses of IL-2 plus CD95 agonist antibody positively regulates LC3B accumulation. We did not observe apoptosis under any of the treatments carried out. In conclusion, cervical tumour cells can use the IL-2 and CD95 pathways to induce their proliferation and potentially activate cytoprotective mechanisms for survival.